STABLE ISOTOPE STUDY OF CALCITE CEMENT AND VEINS FROM NORTHLAND ALLOCHTHON AND BASAL WAITEMATA GROUP ROCKS, NEW ZEALAND - Aadil, N.; D. Sohail, G. M.; Rehman, T.; Sohail, S. (The Nucleus, 2013)
This paper provides stable isotope studies of calcite cement and vein calcite from units of Northland Allochthon rocks and the lower part of the overlying Miocene Waitemata Group of New Zealand to establish the source of C and O in the sediments. Veins in Cretaceous claystones beneath the Miocene rocks have Î´18OPDB of -4.5 to -5.94, and Î´13CPDB of +2.8 to +14.94. Veins in Oligocene Mahurangi limestone have Î´18OPDB of -1.11 to -10.14 and Î´13CPDB of +1 to +1.84. Veins in basal Waitemata Group have Î´18OPDB of -9.18 to -10.62, and Î´13CPDB of -10.5 to -17.15. Results indicate that the depositing solutions were probably less saline than seawater; however, the wide variation in C values suggests different sources of carbon in the three samples. Calcite cement in the concretions of Cretaceous age, sandstones has Î´ 18OPDB of 7.6 to -10.6, and Î´13CPDB of -20 to -23.6. More negative of O values than the veins in the Cretaceous rocks suggest formations at different time when pore solutions were even further from marine composition. The strongly negative C values indicate origin from oxidation of organic matter. The difference from the veins in the Cretaceous rocks supports the evidence of different source waters. Calcite cements of sandstone concretions from basal Miocene have Î´ 18OPDB of -4.3 to -3.5, and Î´13CPDB of -7.1 to +1.3. Both O and C values support an early diagenetic origin, indicated by slightly modified seawater source.